Military family dynamics in transition: The experiences of young people when their families leave the Australian Defence Force. Issue 3 (30th December 2021) - Wells, Hannah; Heinsch, Milena; Brosnan, Caragh; Kay‐Lambkin, Frances
Abstract: Many families experience a smooth transition from military to civilian life. However, some can face intense challenges and significant disruption to family functioning, including mental health and substance use issues, domestic and family violence, marriage dissatisfaction or family breakdown, and even suicide. While some research has examined these transition experiences of ex‐serving men and women, few studies have focused on their children. Understanding the challenges and opportunities the military–civilian transition poses for young people is crucial if we are to develop effective interventions to meet their needs in the future. This paper reports on findings from a qualitative study that retrospectively explored the experiences of young people from ex‐serving Australian Defence Force families when their parents left the military. Using thematic analyses, three key themes relating to military family dynamics were identified: (i) increased mental health stress, (ii) shifts in family relationships and dynamics, and (iii) domestic violence and maltreatment. These themes are discussed alongside the existing literature, revealing the challenges experienced by young people during the military–civilian transition, but also their innate strengths and resources in coping with this major life event. Implications for the social work profession and for developing effective transition supports for young people from ex‐serving families are considered.